Artificial Intelligence and its Effectiveness in Designing Contemporary Interior Spaces (Al-Academy, 2025)
In recent years, the field of artificial intelligence has witnessed tremendous development, intervening in many aspects of life. Artificial intelligence is no longer just a new technology; it has become an effective tool relied upon by designers to achieve innovative and effective designs that meet the needs and aspirations of users and add new dimensions to sustainability and environmental efficiency. Interior design is an art that evokes organization and comfort, manifested by enhancing the performance and aesthetic value of a specific space. When it comes to interior design, as in many disciplines, artificial intelligence has begun to make inroads into this field and is increasingly asserting its presence. Based on the above, the researcher finds himself faced with a question that could embody the current research problem, as follows: "How effective are artificial intelligence and its applications in the field of interior design, and what is its role in promoting the principles of sustainability in the design of interior spaces?" Therefore, the researcher finds it necessary to understand the potential of artificial intelligence and its application in architecture and interior spaces, the reasons for asserting its presence as an advanced technology with a positive impact on interior spaces, and the extent to which it can be employed in the designs of local public institutions. The study aimed to demonstrate the effectiveness of artificial intelligence in interior design and its role in promoting environmental sustainability within interior spaces. To achieve the research objective, the researcher conducted a comprehensive study comprising three chapters. The first addressed the research problem, its importance, and its objective, as well as the boundaries and definitions of the terms used. The second chapter contained the theoretical framework, which in turn included two sections. The first addressed the effectiveness of artificial intelligence and its applications in interior design. The second section addressed the role of artificial intelligence in achieving sustainability in interior spaces. The third chapter concluded with a set of conclusions and several recommendations. The most important conclusions include:1. Artificial intelligence is an effective tool in developing contemporary interior spaces, as it contributes to improving design processes in terms of speed and accuracy, and the ability to process large amounts of information in a manner that exceeds traditional human capabilities.Artificial intelligence is effective in enhancing interaction between the user and the interior space, through intelligent systems capable of responding to environmental and behavioral changes, leading to more flexible and dynamic designs.3. Artificial intelligence is an effective tool for achieving sustainability in indoor spaces, not only by reducing environmental impact, but also by improving the quality of life within these environments